Associated factors with otitis externa in the city of Antsiranana, Madagascar - Randrianandraina, Patrick M.; Razafimahatratra, Mamy J. J.; Solo, Corinne E.; Valisoa, Angelo H.; Razay, Nathalie C.; Ramilison, Heritsilavo E.; Rakotoarisoa, Andriarimanana H. N. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Otitis externa is common in medical practice. This study aims to identify the contributing factors of otitis externa in the city of Antsiranana, Madagascar. Methods: This is an analytical case-control type study, concerning patients with otitis externa, seen from January to July 2019, at the university hospital of place Kabary and at the grand Pavois medical practice, all in Antsiranana. The epidemiological, behavioural and clinical parameters were evaluated. Results: We included 153 patients, among which 51were cases and 102 controls. The average age was 32.9 years (±19.41). The occurrence of otitis externa was significantly associated with the existence of a history of otitis externa, as well as ear cleaning 4 to 6 times per week (p=0.00; OR=46.17; CI=5.90-361.02). The diabetes exposure ratio was 18.79 in the ‘cases’ (p=0.00; CI=2.27-154.88), this ratio was 10.71 in the event of repeated swimming in pool (p=0.00; CI=2.22-51.70), 3.94 in case of ear cleaning with the cotton swab (p=00; CI=1.34-11, 60), and 2.23 when using headphones (p=0.02; CI=1.05-4.75). The treatment of a previous otological pathology was a protective factor against otitis externa (OR=0.1500, p=0.0159, CI=0.0259-0.8689). Conclusions: The occurrence of otitis externa is related to well define daily behaviours and to other associated clinical factors. Managing these risk factors is the first step in treatment of otitis externa.